2009
DOI: 10.1183/09031936.00001709
|View full text |Cite
|
Sign up to set email alerts
|

Stress failure plays a major role in the development of high-altitude pulmonary oedema in rats

Abstract: Hypoxia and exertion are considered as the two main factors in the development of high-altitude pulmonary oedema (HAPE), however its pathophysiology remains unclear. Therefore, we established a model in which 32 Sprague-Dawley rats were randomly assigned to normoxic rest, hypoxic rest, normoxic exercise and hypoxic exercise.An altitude of 4,700 m was simulated using hypobaric hypoxia, while exercise consisted 48 h walk with 15-20 min breaks every 4 h. Arterial blood gas, bronchoalveolar lavage (BAL), lung wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Rats exposed to physiologically relevant levels of hypobaric hypoxia developed elevated bronchoalveolar lavage (BAL) fluid total protein, albumin and red blood cell concentrations. These changes were more evident in animals subjected to higher levels of physical exercise under hypoxic conditions and were not observed in normoxic resting animals 31) .…”
Section: Pathophysiology Of Hapementioning
confidence: 84%
See 1 more Smart Citation
“…Rats exposed to physiologically relevant levels of hypobaric hypoxia developed elevated bronchoalveolar lavage (BAL) fluid total protein, albumin and red blood cell concentrations. These changes were more evident in animals subjected to higher levels of physical exercise under hypoxic conditions and were not observed in normoxic resting animals 31) .…”
Section: Pathophysiology Of Hapementioning
confidence: 84%
“…The increasing pressure on the capillaries imparts excessive stress on the collagen and the extracellular matrix of the alveolar capillary barrier, which in turn leads to the mechanically induced breaks in the blood gas barrier, also described as the "stress failure" of pulmonary capillaries by West and colleagues (1991) 30) . A study using a rat model by Bai et al in 2010 showed a direct relation between the histological evidence of pulmonary capillary stress failure and progression of an illness similar to HAPE 31) . Rats exposed to physiologically relevant levels of hypobaric hypoxia developed elevated bronchoalveolar lavage (BAL) fluid total protein, albumin and red blood cell concentrations.…”
Section: Pathophysiology Of Hapementioning
confidence: 99%
“…7,33 Furthermore, under hypobaric hypoxia especially with exercise 49 and high-pressure ventilation, 50 the intact lungs are injured mechanically and exhibit rupture of the alveolocapillary membrane or a change in the pulmonary permeability. Digesting collagen greatly decreases stiffness, 51 similarly as a decrease in the number of collagen cross-linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been previously shown that rats, rapidly decompressed to extremely low barometric pressures, developed evidence of stress failure [27] the link to HAPE had not been fully established. The strength of the work of BAI et al [26], is the comprehensive and well controlled nature of the study design: animals who were subjected to physiologically relevant levels of hypobaric hypoxia (420 mmHg, altitude ,4,700 m) developed an increase in lung wet-to-dry ratio, and bronchoalveolar lavage fluid total protein, albumin and red blood cell concentrations, indicating that these animals had increased lung water and …”
mentioning
confidence: 99%
“…In a carefully controlled study published in this issue, BAI et al [26], working with a rat model, link for the first time direct histological evidence of pulmonary capillary stress failure and the development of a HAPE-like illness. Although it has been previously shown that rats, rapidly decompressed to extremely low barometric pressures, developed evidence of stress failure [27] the link to HAPE had not been fully established.…”
mentioning
confidence: 99%